Effect of short term match program on certain blood lipids of football players - Cengiz, Şebnem; Çınar, Vedat; Pala, Ragıp; Dündar, Aykut (My University, 2013)
Purpose: In this study, it is aimed to determine the effect of match program of 10 days and in chronic medium intensity on the Triglyceride, Cholesterol, HDL and LDL blood values of football players. Instruments and Methods: Research is performed on 18 healthy male footballer subjects. All subjects participated in match program for total of 7 days, 90 minutes on one day within the framework of a 10 days match program. Blood samples were taken from all subjects in resting position before starting to the match program and 2 hours after the end of the last match. Triglyceride, Cholesterol, HDL and LDL levels were specified in the blood samples received. Findings: According to the data obtained at the end of the match program, triglyceride level has decreased significantly in comparison to the values before the match program (p<0.05). Same result was obtained for the cholesterol levels, similarly blood values taken at the end of the match program as the posttest measurements were lower than the pretest measurements, thus the difference between was statistically important (p<0.05).At the end of the match program, there was a significant decrease in the posttest measurements of LDL in comparison to the pretest measurements (p>0.05). It is determined that HDL values after the match recorded an increase in comparison to the values before the match. Thus, the difference between is statistically significant (p<0.05). Results: According to the results of the study, short-term match program caused changes in the Cholesterol, HDL and LDL blood values.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Blood; Lipids; Footbaal; Match; Training